Matrix support in mental health in primary care: the vision of supporters and nurses - Gustavo Costa de Oliveira; Jacó Fernando Schneider; Leandro Barbosa de Pinho; Marcio Wagner Camatta; Cíntia Nasi; Andréa Noeremberg Guimarães; Maria Eduarda de Lima Torres (Universidade Federal do Rio Grande do Sul, 2019)
Abstract Objective: To understand the view of supporters and nurses on matrix support mental health actions in Primary Health Care. Method: A qualitative and phenomenological study, with Alfred Schutz's framework of phenomenological sociology. The study was conducted with five supporters and 22 nurses from Basic Health Care Units in the city of Porto Alegre. The participants' intentions and expectations, captured through a phenomenological interview, made up the corpus of analysis. Results: The supporters have the intention, given the actions of the matrix support, to improve mental health care for the user. On the other hand, the nurses expect support to the health units, which reveals nonconformities in the mental health practices instituted in the basic network. Final considerations: Knowing the motivations of supporters and nurses can be a powerful strategy for consolidating public policies with a view to the psychosocial way in the territory.